Analisis partisipasi masyarakat dalam pengembangan usaha wisata berbasis industri kreatif di Kampung Wisata Kreatif Cigadung - Maryonoputri, Laeticia Viergiani; Rahmafitria, Fitri; Rahman, Gilang Nur (Trend and Future of Agribusiness, 2024)
Background: This research is based on the development system in KWK Cigadung which has not yet run optimally and the phenomenon of economic disparity that occurs among business actors who still stand individually. Findings: The aim of this research is to analyze the forms of community participation in the development of creative tourism businesses in the Creative Tourism Village of Cigadung. Methods: A qualitative descriptive approach was used in this study with data triangulation techniques through observation, documentation, and interviews conducted with related community communities. The theory of community participation and the theory of business development) served as the basis for analyzing community participation and identifying the potential and obstacles of participation in business development. Conclusion: The results of the study indicate that the dominant form of participation is demonstrated by business actors through their skill potential in creative product diversification, skill training, and batik workshops as well as cultural performances. The participation provided contributes significantly to the increase in income and product quality for several business actors. However, the main obstacle found is the lack of participation from human resources in supporting development and a poorly coordinated management system, limited management in compiling tourism packages causing disparities among business actors, and suboptimal marketing strategies. Recommendations from this research include evaluation and improvement of community meetings for program development, development of structured tourism packages through community collaboration in combining diverse attractions, and enhancement of digital marketing strategies through collaboration with stakeholders.